The Effectiveness of the School Environment Introduction Period (MPLS) Activities in Improving the Social Adaptation of New Students at SMA Negeri 1 Kutambaru - Dahrim , Dahrim (Sean Institute, 2025)
The School Environment Introduction Period (MPLS) is an important initial stage in supporting the social adaptation process of new students. This study aims to determine the effectiveness of MPLS activities at SMA Negeri 1 Kutambaru in helping new students adapt socially and identify factors that support or hinder this adaptation process. The method used was a descriptive quantitative approach with data collection techniques in the form of questionnaires and observations during three days of MPLS activities. The results showed that the majority of new students had a high level of social adaptation, with an average score of 4.02. As many as 87% of students found it easy to make new friends, 83% were more confident in interacting, and 79% understood and were willing to obey school rules. Observations also showed that the atmosphere of the activities was active, collaborative, and conducive. These findings are in line with Vygotsky's theory that emphasizes the importance of social interaction in individual development. In conclusion, MPLS activities designed in an educational, participatory, and systematic manner have proven effective in supporting the social adaptation of new students, although further assistance is still needed for a small number of students who show obstacles in interacting.